2011
DOI: 10.1007/s10059-011-0021-y
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Sperm-Specific Proteins by IFE-1, a Germline-Specific Homolog of eIF4E, in C. elegans

Abstract: IFE-1 is one of the five C. elegans homologs of eIF4E, which is the mRNA 5′ cap-binding component of the translation initiation complex eIF4F. Depletion of IFE-1 causes defects in sperm, suggesting that IFE-1 regulates a subset of genes required for sperm functions. To further understand the molecular function of IFE-1, proteomic analysis was performed to search for sperm proteins that are downregulated in ife-1(ok1978); fem-3(q20) mutants relative to the fem-3(q20) control. The fem-3(q20) mutant background wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 20 publications
(28 reference statements)
0
22
0
Order By: Relevance
“…mRNAs from these latter two genes increase 2.2-and 2.4-fold after P-granule RNAi. Interestingly, genes regulated by P granules do not include those encoding SPE-44 and ELT-1, which have been shown to promote sperm-specific transcription (Kulkarni et al, 2012;Shim, 1999), or IFE-1, which promotes sperm-specific translation (Kawasaki et al, 2011).…”
Section: Expression In P-granule-depleted Germlinesmentioning
confidence: 99%
See 1 more Smart Citation
“…mRNAs from these latter two genes increase 2.2-and 2.4-fold after P-granule RNAi. Interestingly, genes regulated by P granules do not include those encoding SPE-44 and ELT-1, which have been shown to promote sperm-specific transcription (Kulkarni et al, 2012;Shim, 1999), or IFE-1, which promotes sperm-specific translation (Kawasaki et al, 2011).…”
Section: Expression In P-granule-depleted Germlinesmentioning
confidence: 99%
“…This small time window, when PGL-1/3 begins to be cleared from P granules in primary spermatocytes until spermatid budding, coincides with the onset of transcription and subsequent translation of sperm-specific mRNAs. IFE-1, which facilitates this sperm-specific translation (Henderson et al, 2009;Kawasaki et al, 2011), physically interacts with PGL-1 (Amiri et al, 2001). This interaction is predicted to repress IFE-1 activity until PGL-1 is cleared from P granules at the onset of spermatogenesis (Amiri et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that a ubiquitous eIF4E isoform might carry out global translation initiation, whereas the other isoforms might be involved in more specific processes of translation (Hernández and VazquezPianzola, 2005). Work in C. elegans supports this, as IFE-1, a germline-specific eIF4E, is required for sperm (Amiri et al, 2001;Kawasaki et al, 2011) and oocyte (Henderson et al, 2009) maturation, loss of IFE-2 affects chromosome segregation at meiosis (Song et al, 2010), and IFE-4 is involved in translating only a small set of neural and muscle mRNAs involved in egg laying (Dinkova et al, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…Five isoforms of eIF4E (IFE-1-IFE-5) are expressed in the nematode C. elegans (Jankowska- Anyszka et al, 1998;Keiper et al, 2000). We have previously shown that individual isoforms regulate a unique subset of mRNAs in a tissue-specific manner (Amiri et al, 2001;Dinkova et al, 2005;Henderson et al, 2009;Kawasaki et al, 2011;Song et al, 2010). Given that all IFEs bind to mRNA caps, these findings suggest a selective cap-dependent regulation that goes beyond mTOR regulation.…”
Section: Introductionmentioning
confidence: 99%